Tandem malonate-based glucosides (TMGs) for membrane protein structural studies - Hazrat Hussain (Nature Portfolio, 2017)
Abstract High-resolution membrane protein structures are essential for understanding the molecular basis of diverse biological events and important in drug development. Detergents are usually used to extract these bio-macromolecules from the membranes and maintain them in a soluble and stable state in aqueous solutions for downstream characterization. However, many eukaryotic membrane proteins solubilized in conventional detergents tend to undergo structural degradation, necessitating the development of new amphiphilic agents with enhanced properties. In this study, we designed and synthesized a novel class of glucoside amphiphiles, designated tandem malonate-based glucosides (TMGs). A few TMG agents proved effective at both stabilizing a range of membrane proteins and extracting proteins from the membrane environment. These favourable characteristics, along with synthetic convenience, indicate that these agents have potential in membrane protein research.